Local conformational variations observed in B-DNA crystals do not improve base stacking: computational analysis of base stacking in a d(CATGGGCCCATG)(2) B<-->A intermediate crystal structure - Poner, J; Florián, J; Ng, H L; Poner, J E; Packová, N (Nucleic acids research, 2000)
The crystal structure of d(CATGGGCCCATG)(2) shows unique stacking patterns of a stable B<-->A-DNA intermediate. We evaluated intrinsic base stacking energies in this crystal structure using an ab initio quantum mechanical method. We found that all crystal base pair steps have stacking energies close to their values in the standard and crystal B-DNA geometries. Thus, naturally occurring stacking geometries were essentially isoenergetic while individual base pair steps differed substantially in the balance of intra-strand and inter-strand stacking terms. Also, relative dispersion, electrostatic and polarization contributions to the stability of different base pair steps were very sensitive to base composition and sequence context. A large stacking flexibility is most apparent for the CpA step, while the GpG step is characterized by weak intra-strand stacking. Hydration effects were estimated using the Langevin dipoles solvation model. These calculations showed that an aqueous environment efficiently compensates for electrostatic stacking contributions. Finally, we have carried out explicit solvent molecular dynamics simulation of the d(CATGGGCCCATG)(2) duplex in water. Here the DNA conformation did not retain the initial crystal geometry, but moved from the B<-->A intermediate towards the B-DNA structure. The base stacking energy improved in the course of this simulation. Our findings indicate that intrinsic base stacking interactions are not sufficient to stabilize the local conformational variations in crystals.
Keywords: Models, Molecular; krystalizace; párování bází; sekvence nukleotidů; Static Electricity; Computer Simulation; Crystallization; zastoupení bazí; termodynamika; Base Pairing; Solvents; Base Composition; molekulární modely; rozpouštědla; statická elektřina; DNA; Thermodynamics; počítačová simulace; Base Sequence; ohebnost (fyzika); voda; Pliability; Water